Regional Equilibrium Unemployment Theory at the Age of the Internet - Vanessa Lutgen; Bruno Van der Linden (Institute for the Study of Labor (IZA), 2013)
This paper studies equilibrium unemployment in a two-region economy where homogeneous workers and jobs are free to move and the housing market clears. Because of the Internet, searching for a job in another region without first migrating there is nowadays much simpler than in the past. Search-matching externalities are amplified by this possibility and by the fact that some workers can simultaneously receive a job offer from each region. The rest of the framework builds on Moretti (2011). We study numerically the impacts of various local shocks in a stylized US economy. Contrary to what could be expected, increasing matching effectiveness in the other region yields growing regional unemployment rates. We characterize the optimal allocation and conclude that the Hosios condition is not sufficient to restore efficiency. In the efficient allocation, the regional unemployment rates are much lower than in the decentralized economy and nobody searches in the other region.
Keywords: J61; J64; R13; R23; 330; matching; search then move; spatial equilibrium; regional economics; unemployment differentials